2021
DOI: 10.3390/s21010287
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Based Contact Force Control Algorithm for Walking Robots

Abstract: Walking algorithms using push-off improve moving efficiency and disturbance rejection performance. However, the algorithm based on classical contact force control requires an exact model or a Force/Torque sensor. This paper proposes a novel contact force control algorithm based on neural networks. The proposed model is adapted to a linear quadratic regulator for position control and balance. The results demonstrate that this neural network-based model can accurately generate force and effectively reduce errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Zhang and Liang (2019) proposed a hybrid sliding mode impedance control method based on disturbance observer and the experimental results showed that the force tracking performance and robustness of the system were significantly improved. Kim and Kim (2021) proposed a force control method based on neural network in order to suppress unknown interference in the contact force control process and reduce modeling error. The results showed that this method has high applicability to contact force control, but the response time is slow.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Liang (2019) proposed a hybrid sliding mode impedance control method based on disturbance observer and the experimental results showed that the force tracking performance and robustness of the system were significantly improved. Kim and Kim (2021) proposed a force control method based on neural network in order to suppress unknown interference in the contact force control process and reduce modeling error. The results showed that this method has high applicability to contact force control, but the response time is slow.…”
Section: Introductionmentioning
confidence: 99%